Experimental Study on Concrete with Low Calcium Fly Ash as Mineral Admixture - Jayakumar, Muthuramalingam; Yuh, N. (VLB Janakiammal College of Engineering and Technology, 2010)
The hostile marine environment makes any kind of building materials vulnerable in terms of performance and durability. However, one of the best suited materials to be used in these areas is reinforcing concrete. Concrete has been widely known for its tremendous compressive strength, but it also has its shortcomings. Concrete is a porous material, its permeability has a direct relationship with the water/cement ratio used. Concrete with high permeability will cause reinforcing steel to corrode in a higher rate. Low water/cement ratio is often used in production of high performance concrete (HCP) to counter the permeability problem. This will not only produce high strength concrete, but also lower the permeability properties. Concrete will always be a porous material no matter how low the water/cement ratio is.To enhance the impermeability of high strength concrete, mineral admixture such as fly ash is incorporated in the mix design to create a high strength high performance concrete (HSHCP). Fly ash is often used in concrete as a partial substitute for cement, the results of this incorporation shows an overall increase in terms of performance. Available information also show increase in durability performance of concrete in marine environment. This paper presents the durability performance of high strength concrete having different mix design with incorporating varying amount of fly ash content. The performance of the concretes will be evaluated based on some of the test criteria recommended by the Concrete Institute of Australia for evaluating the durability performance of concrete in marine environments.